The aesthetical writings of Giacinto Scelsi - Scelsi, Giacinto 1905-1988 (Rowman & Littlefield, 2023)
"Giacinto Scelsi, an innovative and often controversial force in modern music, has been the subject of a vast amount of literary criticism, philosophical discussion, and performance. For the first time, this volume brings selected writings, spanning from the early 1940s to 1987, into English with historical, social, and cultural contextualization"--